Environmental Corruption Prevention Policies Through Independent Agencies - Mirnawanti Wahab; Rizki Ramadani (Universitas Lampung, 2021)
This article aims to explain the patterns of corruption in the environmental sector (environmental corruption) and the possibility for Independent agencies to address them. Also, to initiate a better policy and supervision against environmental corruption in Indonesia. The research was carried out based on the normative legal method (library research) towards secondary data using a statutory, conceptual, and comparative approach. The results show that the main pattern of environmental corruption involves corrupt actors in bureaucratic institutions that cause weak environmental policies and supervision. The benefit of Independent Agencies with structural and personnel independence is expected to fill the gap in the old bureaucratic management and reduce corruption. The regulatory power of such agencies can also set more stringent environmental policy and supervision. Thus, there needs to be institutional reform in the environmental authorities for future policies by establishing an independent agency. The new agency must also have the power to formulate and enact policies in environmental management and give them authority to investigate and impose sanctions. We also recommend compiling a national strategic program in the form of work synergy between independent agencies in the environmental and anti-corruption sector.